Integrated heterogenous medical database cardiothoracic surgery systems. - Selamat, Mohd Hasan; O. K. Rahmat, Rahmita Wirza; Affendey, Lilly Suriani; Atan, Rodziah; Abdul Kadir, Rabiah; Ghazali, Masitah; Dimon, Mohd Zamrin; Abdul Rahman, Mohd Ramzisham; Ooi, Joanna Su Min (2010)

(untitled)
An integrated healthcare management system accessible by users comprising a plurality user end interfaces (131,132,133,134). The user end interface (131,132,133,134) are connected through a first network (120) to web based applications hosted on one or more application servers (104) comprising one or more modules adapted to perform one or more user functions. There may be preferably one for each user group (131,132,133,134), interacting with each other in real time and selectively accessible to one or more user groups (131,132,133,134). The application server (104) is further connected to a plurality of servers through a second network (110). The plurality of servers include at least one server (101) to store and manages the data selectively accessible at the user end (131,132,133,134) and at least one server to store images (102) selectively accessible at the user end (131,132,133,134).